ASUHAN KEPERAWATAN KELUARGA PADA TAHAP PERKEMBANGAN ANAK REMAJA DENGAN INTERVENSI FISIOTERAPI DADA UNTUK MENURUNKAN INTENSITAS SERANGAN ASMA PADA NY. S RT 001/004 KELURAHAN PERIUK KOTA TANGERANG - Anik Widiastuti,; Alfika safitri,; Hasan Basri, (Nusantara Hasana Journal, 2024)
Bronchial asthma is a respiratory disease that is often found in society. Bronchial asthma is a disease of the airways caused by certain stimuli that attack the trachea and bronchi. According to Basic Health Research (RISKESDAS), the prevalence rate of asthma at all ages in Indonesia is 2.5%. The incidence of asthma is highest in the age group 75 years and over, and begins to decline in the age group 15-24 years. (RISKESDAS, 2018). The nurse's role in providing family nursing care to patients with bronchial asthma is to intervene to help reduce the symptoms caused by asthma by providing non-pharmacological chest physiotherapy therapy and providing education to family members about bronchial asthma. Objective of this research to determine the effect of chest physiotherapy on airway ineffectiveness in asthma sufferers. This research uses a case study method with a nursing care approach for families with bronchial asthma. The data collection instrument uses a family nursing care assessment format through the nursing process of assessment, nursing diagnosis, planning, implementation and evaluation. The implementation results show that chest physiotherapy can reduce symptoms of asthma attacks by increasing oxygen saturation from 94% to 96% after three days of chest physiotherapy. Nurses can provide chest physiotherapy exercises and families are able to demonstrate chest physiotherapy which will continue to be carried out to provide support for providing family nursing care. Chest physiotherapy can be used as a non-pharmacological therapy to reduce the intensity of asthma attacks and overcome the problem of ineffective airway clearance nursing.